Implementação da política de educação inclusiva nos municípios do estado de São Paulo: um estudo de caso do município do Guarujá - Ribeiro, Erika Caracho (2013)
The purpose of this dissertation is to expose some discussions about the issue of implementation of inclusive education policy in municipalities, analyzing the case of the city of Guaruja. This study aims at describing the implementation of inclusive education policy in municipalities, and analyzing its relevant actors’ network. Considering a recent research on the topic, this paper is intended to discuss the federal government influence on implementing this education in subnational governments, and to discuss the federalism issue on education, in the field of inclusive education. The research raised laws, decrees, statements, rules, and key government plans and programs that are connected to the theme, arranging them in a historical perspective. The main theoretical models used in this analysis address the network format and the perspective of playing in implementation of public policies. In order to make these analyses possible, there was an observation of the experience of the city of Guaruja in implementing the inclusive education policy during the years 2009 to 2012. It was introduced data on this policy, which were organized for the present analysis, focusing on municipal management